Chemical composition of Origanum majorana, Mentha spicata and Ocimum basilicum essential oils and their impact on Spodopteralittoralis: toxicity and immune response - Askar, Mofeed; Hafez, Elsayed E.; Saleh, Ahmed A.; Marei, Amal H.; Hussein, Hanaa S.; R., El-Seedi H.; Galal, Fatma H.; Li, Yaohai; Su, Honghua (Frontiers in Plant Science, 2026)
IntroductionThis study presents the essential oils (EOs) derived from Origanum majorana L. (Marjoram), Mentha spicata L. (Spearmint) and Ocimum basilicum L. (Basil), which are explored for their insecticidal potential against Spodoptera littoralis larvae.MethodsEOs were extracted and analyzed using gas chromatography-mass spectrometry (GC-MS), identifying 47, 37 and 27 compounds in O. majorana, M. spicata and O. basilicum, respectively.ResultsMajor constituents include terpinen-4-ol (25.47 %) and sabinene (18.3%) in O. majorana, piperitenone oxide (43.83 %) in M. spicata, and methyl (E)-cinnamate (48.69 %) in O. basilicum. Toxicity assays demonstrated significant larvicidal activity with LC50 values of 1.18 % for O. majorana, 0.43% for M. spicata, and 0.51% for O. basilicum. Furthermore, these EOs notably influenced the expression of defense-related genes in S. littoralis, with treated larvae showing an ~80% increase in PR1, endoglucanase (PR2) and chitinase gene expression compared to controls. Differential display confirmed the amplification of these regulated genes in treated insects.DiscussionThis research underscores the efficacy of EOs from O. majorana, M. spicata and O. basilicum as natural insecticides, providing valuable insights for sustainable pest management through specific gene markers.